O ensino suprerior de administração no Brasil e em Goiás: expansão, privatização e mercantilização no período de 1995-2006 - LIMA, Tereza Cristina M. Pinheiro de (2007)
This research intends to examine the expansion of the undergraduate teaching in Administration, specifically in Brazil and Goias state, through the period of 1995-2006, which was marked by deep transformations in the political, economic and social structures of the country, starting from the mercantilism, privatization and inland of that education level. This project analyzes the expansion of the undergraduate teaching in the context of a Brazilian State Reformation. It takes the politics of undergraduate teaching expansion in Administration within the conjuncture of the transformations in the capitalist way of production in Brazil, exploring, inclusively, the orientations of the neoliberal politics divulged by the multilateral organisms. The implemented government politics represent the crowning of the neoliberal politics in Goias, with predominance for the private teaching (with public budgets), in which the logic is settled by the criteria of the market, of the competition, of the lowest investment and largest profit. The methodological course includes bibliographical research, official documents, state and national organisms websites, as well as websites in IES researched in Goiás, questionnaires and interviews with protagonists of this history. The researched universe included 47 courses of Administration created in the period of 1995 - 2006, which 18 courses are carried out in Goiania, 29 inside the state, 9 in public IES and 38 in private IES. The results of the research indicate a significant growth of the private undergraduate teaching, the narrow relationship of the expansion, privatization and the inland of the undergraduate teaching in Administration. It presents the expansion of the course with its multiple qualifications as market strategy in order to supply the labor market, to generate profits to the educational entrepreneurs, disfiguring the course of Administration. It still indicates that creating courses of Administration was an investment opportunity in the world of businesses, delineating the privatized expansion of the undergraduate teaching in the country and in Goias state